Cyberoperations and sovereignty in international law - FUN, Joel Wei Xuan (Institutional Knowledge at Singapore Management University, 2023)
The cyberspace is sometimes seen as having no jurisdictional boundaries, given that no single state controls the entirety of the cyberspace. At the same time, given how pervasive the cyberspace has become today, many important interests of states now lie in the domain of cyberspace. This uneasy tension has led to many questions involving the intersectionality between the state’s sovereignty over its territory and the cyberspace, which is exacerbated when states use the cyberspace to conduct their myriad operations. This paper seeks to delineate permissible and impermissible cyberoperations and argues that the present international law on sovereignty is sufficiently robust for such delineations.